Role of right dorsolateral prefrontal cortex–left primary motor cortex interaction in motor inhibition in Parkinson’s disease - Zhen Wang; Zhen Wang; Jianing Wei; Yuyu Song; Yuting Li; Yuting Li; Yin Wu; Robert Chen; Robert Chen; Zhen Wang; Jian Zhang; Xiaoyin Tan; et al. (Frontiers in Aging Neuroscience)
BackgroundImpaired motor inhibition in Parkinson’s disease (PD) is associated with functional alterations in the frontal-basal ganglia (BG) neural circuits. The right dorsolateral prefrontal cortex (DLPFC), pre-supplementary motor area (pre-SMA), and primary motor cortex (M1) play key roles in regulating this inhibition. However, the changes in interhemispheric interactions during motor inhibition in PD have not been clearly defined.MethodsWe used dual-site paired-pulse transcranial magnetic stimulation (ppTMS) to examine the interactions between the right DLPFC and pre-SMA and the left M1 in 30 patients with early-stage PD and 30 age-matched healthy controls (HC) during both resting and active conditions, specifically while performing a stop-signal task (SST).ResultsStop-signal reaction times (SSRT) were significantly longer in PD patients compared to HC. The right DLPFC–left M1 interaction, at both short- and long-latency intervals, showed enhanced inhibition in PD following the stop-signal. In PD patients, SSRT was correlated with the inhibition of the right DLPFC–left M1 interaction, with stronger inhibition associated with shorter SSRT.ConclusionThe deficit in reactive inhibition observed in PD is linked to an abnormal modulation of the right DLPFC–left M1 interaction during the stopping process.